2012
DOI: 10.1126/science.1215584
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of TLR5-Flagellin Recognition and Signaling

Abstract: Toll-like receptor 5 (TLR5) binding to bacterial flagellin activates NF-κB signaling and triggers an innate immune response to the invading pathogen. To elucidate the structural basis and mechanistic implications of TLR5-flagellin recognition, we determined the crystal structure of zebrafish TLR5, as a VLR-hybrid protein, in complex with the D1/D2 fragment of Salmonella flagellin, FliC, at 2.47 Å resolution. TLR5 interacts primarily with the three helices of the FliC D1 domain using its lateral side. Two TLR5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
524
3
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 459 publications
(551 citation statements)
references
References 42 publications
16
524
3
5
Order By: Relevance
“…While some LRR ligands such as flagellin bind to the ascending lateral (convex) surface of the LRR-domain, 20 others such as the Spätzle morphogen 21 or the follicle-stimulating hormone 22 interact with the concave LRR surfaces of their respective receptors. In our model the convex surface of the FEI1 ectodomain binds to the surface of the Fas1-2 domain (Figure 3) that is formed by the outward bent β-sheet harbouring the Ser348 residue (marked red in Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…While some LRR ligands such as flagellin bind to the ascending lateral (convex) surface of the LRR-domain, 20 others such as the Spätzle morphogen 21 or the follicle-stimulating hormone 22 interact with the concave LRR surfaces of their respective receptors. In our model the convex surface of the FEI1 ectodomain binds to the surface of the Fas1-2 domain (Figure 3) that is formed by the outward bent β-sheet harbouring the Ser348 residue (marked red in Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Structural analyses of TLR3, TLR4, TLR5, TLR2/1 and TLR2/6 ECDs, and their complexes with typical ligands, demonstrated that each TLR possessed ligand-binding sites or pockets and a dimerizing interface, which allowed for ligand-induced receptor dimerization 46,47 . Although there are multiple ligands for each TLR, it remains unknown whether they share common structural features.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an almost complete set of TLRs has been described in the pufferfish Fugu rubripes and in the zebrafish Danio rerio (12), and, with the exception of TLR4 (13,14), these TLRs seem to be functional orthologs of mammalian TLRs. Thus, they are able to sense the same ligands (15)(16)(17), use similar adaptor molecules for signaling (15), and activate the transcription factor NF-κB (13,15,18). In addition, it has been shown that in zebrafish MyD88 modulates innate immune responses to microbes (19)(20)(21)(22).…”
mentioning
confidence: 99%